Microdebris Analysis of the Central Sewer and the Drainages of the Domus at Pompeiopolis - Mustafa Nuri Tatbul; Massimo Brizzi; Giovanni Ricci; Antonio Abate; Tayyar Gürdal; Luisa Musso (Anadolu Araştırmaları)
In archaeological research, the discard behavior of domestic and industrial spaces can be mostly understood through the inspection of primary refuse contexts such as intra-site garbage pits, cesspits, last activity remains of fireplaces, activity floors, or extramural dumping areas as secondary refuse contexts. Other than these features and refuse contexts in the Late Antique / Early Byzantine period Domus at Pompeiopolis, the central sewer, and the drainage have the potential to provide alternative information related to the consumption, production, and discard behaviors of the households and the community in general. In this paper, microdebris samples taken from the street sewer, the drainage of the Domus, and a direct refuse link from a kitchen space adjacent to the street sewer were analyzed and discussed in consideration of the formation processes of the archaeological record.